Studies on the synthesis of higher alcohol over modified Cu/ZnO/Al2O3 catalyst - Park, Ji In; Jung, Jae-Sun; Noh, Young Su; Lee, Kwan-Young; Moon, Dong Ju (SPRINGER, 2018)
Higher alcohol has been considered as a potential fuel additive. Higher alcohol, including C-2-C-4 alcohol was synthesized by catalytic conversion of syngas (with a ratio of CO/H-2 = 1) derived from natural gas over modified Cu/ZnO/Al2O3 catalyst. Modified Cu/ZnO/Al2O3 catalysts promoted by alkali metal (Li) for higher alcohol synthesis (HAS) were prepared at different pH (6, 6.5, 7, 8, and 9) by co-precipitation to control Cu surface area and characterized by N-2 physisorption, XRD, SEM, H-2-TPR and TPD. The HAS reaction was carried out under a pressure of 45 bar, GHSV of 4000 h(-1), ratio of H-2/CO = 1, and temperature ranges of 240 and 280 A degrees C. It was found that the malachite phase of copper causes the size of copper to be small, which is suitable for methanol synthesis. Methanol and HAS share a common catalytic active site and intermediate. It was also found that the productivity to higher alcohol was correlated with Cu surface area.
Keywords: FISCHER-TROPSCH SYNTHESIS; METHANOL; COBALT